An Optimized Approach to Recover Secreted Proteins from Fibroblast Conditioned-Media for Secretomic Analysis - Paré, Bastien; Deschênes, Lydia T.; Pouliot, Roxane; Dupré, Nicolas; Gros-Louis, Francois (Frontiers in Cellular Neuroscience, 2016)
The proteins secreted by a particular type of cell, the secretome, play important roles in the regulation of many physiological processes via paracrine/autocrine mechanisms, and they are of increasing interest to help understanding rare diseases and to identify potential biomarkers and therapeutic targets. To facilitate ongoing research involving secreted proteins, we revisited cell culture protocols and whole secreted protein enrichment protocols. A reliable method for culturing and precipitating secreted protein from patient-derived fibroblast conditioned-medium was established. The method is based on the optimization of cell confluency and incubation time conditions. The well-established carrier-based TCA-DOC protein precipitation method was consistently found to give higher protein recovery yield. According to our results, we therefore propose that protein enrichment should be performed by TCA-DOC precipitation method 48 hours at 95% of confluence in a serum-deprived culture medium. Given the importance of secreted proteins as a source to elucidate the pathogenesis of rare diseases, especially neurological disorders, this approach may help to discover novel candidate biomarkers with potential clinical significance.